2021
DOI: 10.1021/acs.jafc.0c07572
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Distinct Metabolic Features in Shoot Tips and Roots of Tea Plants (Camellia sinensis): Characterization of MYB Regulator for Root Theanine Synthesis

Abstract: The physiological and metabolic differences between shoot tips and roots of tea plants are significant, and understanding them is required for improvement of tea quality and plant growth. A high-quality full-length transcriptome sequencing on tea plant roots and shoot tips by PacBio SMRT technology was done to gain a further understanding. Approximately 160699 and 166120 full-length transcripts were recovered in roots and shoots, respectively, including 31232 and 41068 novel isoforms and 16960 and 26029 altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 60 publications
2
27
1
Order By: Relevance
“…The C. sinensis genome sequence (Wei et al., 2018) was searched to identify MYB domain‐containing proteins using the hmmsearch package (version 3) and the Basic Local Alignment Search Tool (BLASTP) algorithm with a Hidden Markov Model of MYB Pfam (PF00249) with an E‐value cutoff of 1e−5. All hits were confirmed by SMART analysis (http://smart.embl-heidelberg.de/) on previous full‐length transcriptome data from our lab and other labs (Xu et al., 2017, Zhang et al., 2021).…”
Section: Methodssupporting
confidence: 57%
See 4 more Smart Citations
“…The C. sinensis genome sequence (Wei et al., 2018) was searched to identify MYB domain‐containing proteins using the hmmsearch package (version 3) and the Basic Local Alignment Search Tool (BLASTP) algorithm with a Hidden Markov Model of MYB Pfam (PF00249) with an E‐value cutoff of 1e−5. All hits were confirmed by SMART analysis (http://smart.embl-heidelberg.de/) on previous full‐length transcriptome data from our lab and other labs (Xu et al., 2017, Zhang et al., 2021).…”
Section: Methodssupporting
confidence: 57%
“…AtCPC , encoding a single‐repeat R3‐MYB, is a repressor of anthocyanin biosynthesis in Arabidopsis (Li et al., 2022). Our previous full‐length single‐cell RNA sequencing (RNA‐Seq) data recovered two AtCPC homolog genes, CsCPCa and CsCPCb (Figure 3c, Zhang et al., 2021). Expression pattern analysis revealed that both CsCPCa and CsCPCb were highly expressed in flowers and tender shoots (Figure S8a).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations